Behavior of a water Ferrasol under agroforestry systems in extreme south of the state of Sao Paulo, Brazil - Silva, R. B. [UNESP]; Lima, C. C. [UNESP]; Silva, F. A. M. [UNESP]; Nakamura, R. [UNESP]; Iori, P. [UNESP]; Tellez, F. A.; Rodriguez, A. M.; Sancho, I. M.; Robinson, M. V.; RuizAltisent, M.; Ballesteros, F. R.; Hernando, ECC (Fundacion General Univ Politecnica Madrid, 2014)
The characterization and quantification of the soil water retention, representing the relationship between the water content and energy that takes place is essential to study the relationships between the soil and the water, as made for farmland soil, can also be applied to soils under agroforestry. The aim of this study was to evaluate the impact of agroforestry (SAF) in different stages of succession in the behavioral development of Alfissol water through water retention curves (CRA), field capacity (CC), wilting point (PMP) and water holding capacity of the soil (CAD). The study was conducted in the southern state of Sao Paulo, in the municipality of Cananea / SP, Brazil. SAF's in three stages of succession were evaluated: 1) SAF 12 years, 2) SAF 2.5 years and 3) SAF 1 year. A native forest area was taken as control. The tests were conducted on samples of two layers of the earth (0 to 0.20 m and 0.20-0.40 m). The usage time of agroforestry changed the soil water behavior in relation to native forests, which is used as a reference. Agroforestry already shown using a larger amount of water retention and water available in the surface layers. The results show that agroforestry systems can be, when properly managed, a viable alternative would be to improve water retention in the soil.
Keywords: sustanable management; water; soil conservation